Differentiation of tumoral and non‐tumoral breast lesions using back reflection diffuse optical tomography: A pilot clinical study. Issue 4 (13th April 2021) - Üncü, Yiğit Ali; Sevim, Gençay; Mercan, Tanju; Vural, Veli; Durmaz, Emel; Canpolat, Murat
Abstract: In breast cancer diagnosis, tumoral and non‐tumoral breast lesions differentiation is a challenge. We investigate the feasibility of continuous‐wave back reflection diffuse optical tomography (rDOT) in differentiation tumoral and non‐tumoral breast lesions to solve this problem. Modified Beer–Lambert Law and Rytov solution of diffusion approximation of the radiative energy transfer equation were used together in a continuous wave rDOT system for the near‐infrared imaging the breast with a lesion. The rDOT data were acquired from 15 lesions in 12 patients with a palpable lump after standard clinical examination with mammography, magnetic resonance imaging (MRI), and ultrasonography (US). Also, the measurements symmetrically from the other breast's counterpart were used as a functional imaging base. Histopathological examination revealed the tumor distribution as five invasive ductal carcinomas, one lobular carcinoma, one sclerosing adenosis, and one papilloma. The remaining seven lesions (one hamartoma, one postoperative scar tissue, two cysts, two islands of fibroglandular tissue, and one mastitis) were classified as non‐tumoral breast lesions. They were diagnosed based on clinical, US, mammography, or MRI findings. Tumoral lesions presented a contrast in rDOT tomographic images, whereas non‐tumoral lesions such as hamartoma and cysts did not show any difference except mastitis. In mastitis cases, rDOT showed higher contrast similar to tumoral lesions. After antibiotic treatment, the mastitis area had no high contrast when compared with the healthy breast tissue. We have demonstrated that the rDOT system can differentiate between actual breast tumors from non‐tumoral breast lesions such as cyst, the island of fibroglandular tissue, or hamartoma.